2014
DOI: 10.1155/2014/207659
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoid Colon Migration of an Intrauterine Device

Abstract: Background. Intrauterine devices (IUD) are commonly used birth control methods. Colonic perforation is an infrequent but serious complication of IUD. Case. A 34-year-old woman with 2-years history of IUD, inserted at early puerperal period, presented to gynecologist with chronic pelvic pain and dyspareunia. Radiological assessment revealed that there were two copper-T devices: one in uterine cavity and another in the colonic lumen. Attempts of retrieval with colonoscopy and laparoscopy were unsuccessful. Intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 5 publications
0
23
0
2
Order By: Relevance
“…There are about 30 case reports of colorectal erosions by migrated IUCDs over the past 10 years. The sigmoid colon is more commonly affected than any other parts of the colorectum 10–12. Our search revealed that the sigmoid colon was involved in 60% of the reported colorectal cases penetrated by migrating IUCDs.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…There are about 30 case reports of colorectal erosions by migrated IUCDs over the past 10 years. The sigmoid colon is more commonly affected than any other parts of the colorectum 10–12. Our search revealed that the sigmoid colon was involved in 60% of the reported colorectal cases penetrated by migrating IUCDs.…”
Section: Discussionmentioning
confidence: 88%
“…The other two cases presented with pelvic pain, dyspareunia and vaginal/rectal bleeding. In both cases, the missed IUCDs were found penetrating the sigmoid colon 12 13. One of them had failed attempts at endoscopic and laparoscopic retrievals and was therefore treated by open resection and primary anastomosis 12.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The using rate of IUD as a contraceptive method in developed countries is 9.4% and 16.4% in undeveloped countries (5). In recent years, use of IUD has decreased with the belief that it increases the risk of infection (6).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are studies suggesting that highrisk and asymptomatic patients may be followed up with medical treatment, in case of perforations or migration to intestine, bladder or vessels, IUD should be removed 3,6 . The primarily preferred treatment should be laparoscopic methods for IUDs which were detected to cause perforation of myometrium or abdomen by radiological examinations and laparotomy can be performed if laparoscopy fails because of extensive adhesions 7,8 . The cases who were treated with endoscopic treatment instead of surgical treatment in case of migration of IUD to colon were reported in the literature .…”
Section: Introductionmentioning
confidence: 99%